THE LATEST TERMS THAT HAVE ENTERED THE ARABIC LANGUAGE THROUGH THE PROGRESS OF SCIENCE AND TECHNOLOGY (Archive of Conferences, 2020)
As a result of the continuous development of science and technology in the world, new technical terms are being used. This can also be seen in the lexical richness of the Arabic language.